Equity in out-of-pocket payments for healthcare services: evidence from Malaysia - Abu Baharin, Mohamed Fakhri; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza (Multidisciplinary Digital Publishing Institute, 2022)
Background: Out-of-pocket (OOP) payments are an inequitable mechanism for health financing as their high share of total health expenditures poses a risk of catastrophic healthcare expenditures. This study aimed to assess the distribution and progressivity of OOP payments made by Malaysian households for various group of healthcare services. Methods: This study utilized data from the Malaysian Household Expenditure Survey (HES) between 2014 and 2015, which involved 14,473 households. Distribution and progressivity of OOP payments were measured through their proportion of household consumption, a concentration curves plot and the Kakwani Progressivity Index (KPI). Results: The mean proportion of Malaysian OOP payments for healthcare of household consumption was 1.65%. The proportion increased across households’ consumption quintiles, from 1.03% made by the poorest 20% to 1.86% by the richest 20%. The OOP payments in Malaysia were progressive with a positive KPI of 0.0910. The OOP payments made for hospital-based services were the most progressive (KPI 0.1756), followed by medical products, appliances and equipment (KPI 0.1192), pharmaceuticals (0.0925) and outpatient-based services (KPI 0.0394) as the least progressive. Conclusions: Overall, the OOP payments for healthcare services in Malaysia were progressive and equitable as they were more concentrated among the richer households.